DETECTING FINANCIAL REPORT FRAUD WITH PENTAGON FRAUD ANALYSIS - Liza Widya Hasyim; Sujoko Waluyo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The Pentagon Fraud Theory identifies five elements that drive fraudulent behavior: pressure, opportunity, rationalization, competence, and arrogance, but their empirical relevance may vary across industries. This study aims to examine the influence of these five elements, proxied by Return on Assets, Total Receivables Ratio, Total Accrual Ratio, Director Change, and dualism of positions, on Financial Statement Fraud in banking sector companies on the Indonesia Stock Exchange. The research design used is a causal relationship study with a quantitative approach. The sample in this study was 56 trading sector companies listed on the IDX from 2021 to 2023. The type of data used in this study is secondary data. And the data analysis technique uses multiple linear regression analysis conducted with the help of Eviews software. The results in this study indicate that not all Pentagon Fraud elements are relevant in detecting financial statement fraud, highlighting the importance of a contextual and industry-specific approach in refining fraud risk assessment and contributing to the development of a more nuanced application of the Pentagon Fraud Theory in empirical research.